(untitled) (Research, Society and Development, 2020)
This article aims to develop a systematic literature review to identify characteristics of greenwashing and understand it is effects on consumer loyalty. There was no clipping of dates for making the state of the art, as the subject is recent and few studies that analyze the effects of the practice are available. There were also no filters for the type of document, leaving open articles in a journal and conference proceedings, theses and dissertations, e-books, research reports, among others. The databases used for the search were Web of Science, Scopus and Science Direct. After the search, the articles found were included in the Start software to perform the SLR. After the selections, a volume of 94 publications linked to the subject was obtained, among these, 21 were selected for complete reading and, subsequently, eight publications were used for the final composition of SLR. The characteristics of greenwashing were identified: untruths, false information, symbolic behavior, vague information, among others. The effect of greenwashing on loyalty is the loss of customer confidence in the product or service, in addition to increased skepticism. Therefore, the practice of greenwashing is harmful to the environment and the organization’s business.